Expression of rice resistance gene OsNPR1 against bacterial leaf blight on black rice Cempo Ireng cultivar after salicylic acid treatment - Ikhsan Maulana; Triyaningsih; Tri Rini Nuringtyas; Yekti Asih Purwestri (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2021)
Black rice is an alternative staple food better than white rice. It has lower carbs, but higher antocyanin compared to white rice. Nowadays, black rice consumption has increased, production needs to be increased to accomodate the demand. But, to our knowledge, there is lack of information about black rice resistance against biotic stresses, one of black rice cultivar is Cempo Ireng. This information needed for optimal Cempo Ireng cultivation. In this research, we determined chlorophyl content and analyzed OsNPR1 expression of three cultivars: Java14 (resistant control), Cempo Ireng, and IR64 (susceptible control), against Xanthomonas oryzae (Xoo). All of them were sprayed with salicylic acid (SA) before inoculated with Xoo. IR64 24h had the lowest chlorophyll content (0,576 ± 0,066 mg/g), meanwhile Java14 72h had the highest content (2,358 ± 1,301 mg/g). However, all the cultivars did not show any correlation between them and time after Xoo inoculation. OsNPR1 expression did not show any significant change in Java14 and Cempo Ireng after being inoculation. However, IR64 showed increasing OsNPR1 in 72h and did not change in 96h after inoculation. It indicated that OsNPR1 played important role in IR64 resistance against Xoo, but not in Cempo Ireng and Java14.